Green processing of porous chitin structures for biomedical applications combining ionic liquids and supercritical fluid technology - Silva, Simone Santos (2011)
The application of green chemistry principles in the processing of materials for advanced technologies is a steadily increasing ﬁeld of research. In this work porous chitin-based materials were developed by combining the processing of chitin using ionic liquids (ILs)as a green solvent together with the use of super- critical ﬂuid technology(SCF) as clean technology.Chitin was dissolved in 1-butyl-3-imidazolium acetate,followed by regeneration of the polymer in ethanol in speciﬁc moulds.The IL was removed using Soxhlet extraction and successive steps of extraction with SCF using carbon dioxide/ethanol ratios of 50/ 50 and70/30.The developed porous chitin-based structures (ChIL)can be classiﬁed as mesoporous materials,with very low density and high porosity.The cytotoxicity of ChIL extracts was investigated using L929 ﬁbroblast like cells,and the results demonstrated that the produced materials have extremely lowcytotoxicityl evels.Therefore,the ﬁndings suggest that the porous chitin structures may be potential candidates for a number of biomedical applications,including tissue engineering.